Effect of mulches on soil temperature and soil moisture level under capsicum (Capsicum annuum) crop - SHARMA, UJJAWAL KUMAR; SINHA, JITENDRA; KATRE, P. K. (Journal of Soil and Water Conservation, 2021)
Field experiment was carried out in winter season at research field of Precision Farming Development Centre (PFDC), Department of Horticulture, Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.). The soil temperature was taken at 7:30 am and 2:00 pm. It was observed that at 7:30 am the average soil temperature under black plastic mulch (BPM) is 1.29 and 1.93°C higher as compared to the Paddy straw mulch (PSM) and without mulch (WM) respectively. At 2:00 pm under BPM the average soil temperature increases by 4.6 and 1.62 °C compared to under PSM and WM condition respectively. The average soil temperature under WM is 3.0°C more than PSM condition. It was also found that the soil temperature under PSM was higher than the WM condition. It was found that BPM saves significantly higher soil moisture (49%) as compared to paddy straw mulch at 15 cm soil depth, similarly BPM saves 44% more soil moisture as compared to paddy straw mulch at 30 cm soil depth. BPM with 80% irrigation level gives maximum yield 20802.40 kg/ha, followed by BPM+100% irrigation level which gives 20000.00 kg/ ha. Minimum yield was found in without mulch with control irrigation condition.